Existential Logotherapy in Improving the Meaningfulness of Life of Pre-Prosperous Family Students - Lia Mita Syahri; Firman (Jurnal Pendidikan Indonesia, 2023)
Problems related to poverty in Indonesia have increased every year, the government is trying to overcome poverty, namely the existence of PIP for students of pre-prosperous families, but the problems experienced by students of pre-prosperous families such as feeling unable to reach their goals because of dependence on this assistance. The perceived condition stems from the meaningfulness of life. This study aims to analyze the E-Book of existential logotherapy approach group guidance in improving the meaningfulness of life of pre-prosperous family students. The research method uses quantitative and qualitative, the type of Research and Development (R&D) research. The research subjects were 10 students from 93 students of pre-prosperous families. The result of the research results revealed that (1) the E-Book of group guidance with an existential logotherapy approach was considered feasible to use by counseling teachers, (2) the level of usability of the E-Book of group guidance with an existential logotherapy approach was feasible to use. It can be known the implications of research in the form of a prototype of E-Book group guidance of existential logotherapy approach in increasing the meaningfulness of life of students of pre-prosperous families, so that it can be utilized by counseling teachers in increasing the meaningfulness of life of students of pre-prosperous families.